The Effect of Relaxation Technique (Jacobsen and Benson) on Depression, Anxiety, and Stress in Patients with Multiple Sclerosis - Akbari, Ali; Ahmadi, Forouzan; Jalili, Ebrahim; Khazaei, Salman (Current Psychiatry Research and Reviews, 2020)
Background: Multiple sclerosis (MS) is a chronic disease that affects the central nervous system. Depression, anxiety and stress are the most common psychiatric comorbidities in MS, which can have adverse consequences. The aim of this study was to determine the effect of relaxation (Jacobson and Benson) technique on depression, anxiety and stress in MS patients. Methods: This clinical trial was conducted since December 2016 to March 2017 in the Multiple Sclerosis Association and the Neurology Clinic of Farshchian Hospital (Sina) in Hamadan. Sixty patients with multiple sclerosis were randomly assigned to two experimental (n=30) and control (n=30) groups. The control group received routine care and experimental group received the relaxation technique (Jacobson and Benson) in 8 sessions of 60-minute twice a week for 4 weeks in addition to receiving routine care. The DASS-21 scale was completed by samples before and after the intervention. Results: Results of the study showed that in the intervention group, the scores of depression, anxiety and stress after using relaxation (Jacobson and Benson) was decreased significantly (P<0.05), while in the control group no significant decrease was observed (P<0.05). Conclusion: The results of this study showed that relaxation (Jacobson and Benson) is effective in reducing depression, anxiety and stress in patients with multiple sclerosis. Therefore, in addition to prescribing medication, it is suggested that complementary therapies be performed for these patients.
Keywords: stress